2011
DOI: 10.1186/1465-9921-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis gene expression in murine endothelial cells during post-pneumonectomy lung growth

Abstract: Although blood vessel growth occurs readily in the systemic bronchial circulation, angiogenesis in the pulmonary circulation is rare. Compensatory lung growth after pneumonectomy is an experimental model with presumed alveolar capillary angiogenesis. To investigate the genes participating in murine neoalveolarization, we studied the expression of angiogenesis genes in lung endothelial cells. After left pneumonectomy, the remaining right lung was examined on days 3, 6, 14 and 21days after surgery and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Our studies demonstrated 1) significant displacement of the heart and cardiac lobe within 3 days of surgery, and 2) coincident changes in peripheral lung mechanics. The changes in both the anatomic configuration of the thorax and the impedance measurements within the lung preceded the previously described peaks in growth-associated gene transcription [13, 15]. Further, the peripheral mechanical changes in the lung resolved with compensatory growth.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our studies demonstrated 1) significant displacement of the heart and cardiac lobe within 3 days of surgery, and 2) coincident changes in peripheral lung mechanics. The changes in both the anatomic configuration of the thorax and the impedance measurements within the lung preceded the previously described peaks in growth-associated gene transcription [13, 15]. Further, the peripheral mechanical changes in the lung resolved with compensatory growth.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies of post-pneumonectomy lung cells [12], including endothelial cells [13, 14] and alveolar macrophages [15], have demonstrated an unexpected transcriptional time course; that is, gene transcription and cell proliferation that are minimal at 3 days, but peak 6 to 7 days after pneumonectomy. Distinct from the stretch responses studied in vitro—typically detected within hours of the stretch signal—these results indicate that post-pneumonectomy mechanics may not be optimally characterized as an immediate one-time stretch signal, but rather as dynamic anatomical and mechanical adaptations to the post-pneumonectomy thorax that occur over days to weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Within 10 to 14 days of pneumonectomy, there is a significant increase in the total number of endothelial cells (29). This increase in endothelial cells parallels a 25% and 33% increase in the number of alveoli at Days 6 and 21 following pneumonectomy, respectively (7).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the unique structure of the lung facilitated not only the isolation of these migrating progenitor cells, but also the characterization of their transcriptional profile. Our study demonstrated that blood-derived cells, expressing the CD34 surface molecule, directly contributed to murine postpneumonectomy angiogenesis, based on several lines of evidence: (1) The peak of CD34 1 cell migration was at 7 days-timing that coincided with the peak of lung angiogenesis (29). (2) Approximately 17.0% of migrating CD34 1 cells were undergoing active cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Red cells were lysed using a blood cell lysis buffer (BD PharmLyse, BD Biosciences) as described (30). Lung single cell suspensions were co-stained with CD31 and CD45 antibodies (BD Biosciences), and CD31ϩ cells were sorted out of the CD45 cell population.…”
Section: Methodsmentioning
confidence: 99%